Dividend policy: a comparison on companies listed belonging to PSI20 and BEL20 - Barra, Tânia Isabel Santos (2017)
The factors that drive dividend policy of a company have been the subject of extensive research over time, sometimes there are conflicts regarding the behavior of such earnings. The dividend is the return that investor receives from a company by the profits of this, by their percentage ownership. The study attempts to find the determinants of dividend policies. A sample of companies of PSI-20 and BEL-20 has been considered for the period from 2008 to 2013. Through the use of multivariate linear regressions, three dependent variables, dividend Rate, Dividend Payout and Dividend Yield have been studied. The regression results show that profitability is most significant factor for the decision to distribute dividends. Subsequently the most important determinants obtained were capital structure, growth opportunities, size and interest expenses.